용성 및 불용성전극을 이용한 무전해 니켈 도금 산세 폐액 처리 - 김영신(Young Shin Kim); 전병한(Byeong Han Jeon); 구태완(Tai Wan Koo); 김영훈(Young Hun Kim); 조순행(Soon Haing Cho) (Daehan hwan'gyeong gonghag hoeji, 2016)
In order to treat electrolysis nickel plating pickling wastewater to meet the effluent limit less than 3.0 mg/L, the electrolysis process by using soluble and insoluble electrode were studied. Electrolysis using soluble electrodes has a characteristic of easy elution from the electrode which the insoluble electrodes close not release metal from the electrode. For these reasons, there exist different characteristics in nickel removal efficiency, purity of nickel sludge. With this connection, the feasibility test were concluded to develop optimal conditions for the treatment of pickling wastewater electrolysis by using soluble electrodes, insoluble electrodes. Optimal condition of current density, pH were derived from the pickling wastewater using insoluble electrodes. It was concluded the highest removal efficiency of nickel at the operation condition of at pH 9, current density of $15mA/cm^2$. At these conditions, 95.3% purity of nickel sludge was achieved, iron content was 2.9%. Optimal condition when using soluble electrodes was derived current density of $10mA/cm^2$, pH 9. Purity of nickel sludge was 77.3%, iron content was 21.0%. 50.7% and 24.2% of operating cost can be saved by the use of soluble electrodes and the use of insoluble electrodes, respectively. 무전해 니켈 도금 산세 폐액을 강화된 니켈의 배출허용기준 3.0 mg/L 이하로 처리하기 위해서는 기존 처리방법의 단점을 보완한 처리방법의 개발이 필요하다. 용성전극 및 불용성전극을 이용한 전기분해 처리방법은 공통적으로 무전해 니켈 도금 산세 폐액을 효과적으로 처리할 수 있다. 그러나 용성전극은 전극으로부터 금속이 잘 용출되는 특징을 갖는 반면 불용성전극은 금속이 용출되지 않는 차이점을 갖고 있어 니켈 제거 효율 및 니켈 슬러지 순도에서 서로 다른 장단점이 존재한다. 이에 본 연구에서는 용성전극 및 불용성전극을 이용한 전기분해 방법으로 무전해 니켈 도금 산세 폐액을 처리하기 위한 최적조건을 도출하고, 두 전극을 이용한 방법의 장단점을 조사하였다. 실험결과 불용성전극을 사용하였을 때 처리수의 효율적인 니켈 제거를 위한 최적조건은 전류밀도 $15mA/cm^2$ 이상, pH 9 이상으로 도출되었고 이 조건에서 니켈 슬러지의 순도는 95.3%로 나타났으며, 슬러지 내 철 함량은 2.9%로 조사되었다. 용성전극을 사용하였을 때의 최적 조건은 전류밀도 $10mA/cm^2$ 이상, pH 9 이상으로 도출되었으며 최적조건에서 니켈 슬러지 순도는 77.3%, 슬러지 내 철 함량은 21.0%로 조사되었다. 처리비용을 기존의 처리비용과 비교하여 용성전극 사용시 50.7%, 불용성전극 사용시 24.2% 저감시킬 수 있는 것으로 조사되었다.